Being-child with asthma: assuming its particularities and dealing with restrictions - Karina Machado Siqueira; Isabela Cristine Ferreira Fernandes; Juliana Chaves Araújo; Ana Karina Marques Salge; Thaíla Corrêa Castral; Maria Alves Barbosa (Universidade Federal de Goias, 2017)
The study aimed to comprehend how children with asthma and their families perceive themselves in their experience with the chronic disease and, how they develop their coping ways and care. We conducted a phenomenological study, with five families of children with moderate or severe asthma. Data collection occurred through interviews with the children and their families, during home visits, between September of 2013 and January of 2014. From the child's perspective, the difficulty of dealing with fears, frustrations, and constraints related to the disease and treatment was apparent, especially at school. Family members emphasized the restrictions imposed in the child's life and family environment, besides mentioning care attitudes demonstrating overprotection. Professionals involved in attention to childhood asthma need to value the child's potentialities and the family autonomy in care actions, favoring the experience with the chronic disease and the empowerment for care.